Moral And Ethics in a Government Perspective - Muhammad Fajar Sidik; Wulan Kurniasih; Ibnu Rusydi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The research carried out by the writing team aims to improve the quality of morals, ethics and morals, especially in the government environment. The research method we use is a mixed research method, namely field interviews and using sources from books. The conclusion from our research results is the importance of implementing good morals, ethics and morals in the government environment, to create the best possible service to the community. And this research contains important matters relating to morals, ethics and morals in the government environment.